Serum IgM Levels and Hepatitis D Virus Co-Infection in HBsAg-Positive Patients in Abakaliki, Nigeria - Azibanyam, Okosigha Saviour; Kenneth, Imarenezor Edobor Peter; Ifeoma, Anyiam Vivian (African Journal of Biochemistry and Molecular Biology Research, 2025)
Hepatitis delta virus (HDV) is a defective RNA virus that relies on co-infection with Hepatitis B virus (HBV) for its replication. This study aimed to identify HBsAg-positive patients co-infected with HDV and quantify serum IgM levels in a hospital-based population in Abakaliki, Ebonyi State, Nigeria. A cross-sectional analytical study was conducted among 1,000 patients attending the Federal Teaching Hospital Abakaliki (FETHA) and Mile 4 Hospital Ishieke. HBsAg-positive individuals were identified using a rapid diagnostic kit, while HDV-IgM was detected using ELISA. Among the 1,000 participants, 89 (8.9%) tested positive for HBsAg, and of these, 5 (5.6%) were also positive for HDV-IgM, indicating active co-infection. HDV co-infection prevalence was higher among females (7.7%) compared to males (2.7%), and significantly higher among married individuals (6.9%) than singles (3.2%) (p < 0.05). Age-specific analysis revealed the highest co-infection rate (10%) among individuals aged 29–33 years, while no cases were recorded in the 34–45 years age group. Geographically, patients from Mile 4 Hospital had a higher co-infection rate (7.5%) than those from FETHA (2.8%). Educational status and occupation also influenced prevalence; tertiary-educated individuals had the highest rate (13.6%), while no cases were reported among those with only primary education. Students recorded a prevalence of 8.9%, with no co-infections detected among traders or housewives. Among clinical subgroups, pregnant women had a higher co-infection rate (9.5%) compared to blood donors (2.1%). These findings underscore the importance of routine HDV screening among HBsAg-positive patients, especially in high-risk groups, and the urgent need for targeted public health interventions to reduce the burden and severity of HBV/HDV co-infection in Nigeria. Further research is warranted to better understand the epidemiological dynamics and clinical implications of co-infection.